The reconciliation process in post-apartheid South Africa through Zakes Mda’s Madonna of Excelsior - Jujar Singh, Hardev Kaur; Mani, Manimangai (Universiti Putra Malaysia Press, 2013)
At the present moment in history, there is a renewed interest in defining and redefining nationhood in the processes of dealing with past and reconciliation. Discourses of past and reconciliation have emerged in recent years in nations struggling with the legacies of colonialism. These would include the injustices and oppression inflicted on those natives who could not defend their motherland from oppressors. One such country, South Africa faced forty-six years of atrocious colonization known as apartheid or racial segregation where the blacks and coloured were suppressed by the white colonial masters. Despite apartheid being abolished in 1994, Democratic South Africa is still plagued with social ills and there is still a widespread of racial discrimination between the whites and the blacks. The Truth and Reconciliation Committee was set up right after apartheid was abolished, to help facilitate a truth recovery process. Forgiveness has been forwarded yet redemption and reconciliation are somewhat elusive, as discrimination and instability still exist due to the stigma apartheid has left. This research paper “Apartheid and the Reconciliation Process in the Post-Apartheid South Africa” looks into the novel by Zakes Mda entitled The Madonna of Excelsior, which deals with the issues of the process of reconciliation between the present and the past. In this paper, we investigated if the masses are willing to forget the past in order to create a better future for the new generation of the new South Africa.